Effect of ion irradiation on the surface energy of deposited coatings - Eremin E. N.; Guchenko S. A.; Kasymov S. S.; Yurov V. M.; Vedyashkin M. V. Maxim Viktorovich (Physical and chemical phenomena in inorganic materials in radiation, electrical and thermal fields, 2017)
Title screen